Insecticidal potential of agroecological sprays in the control of cabbage curuquerê, Ascia monuste orseis (Lepidoptera: Pieridae) (Research, Society and Development, 2023)
The objective of this work was to evaluate the insecticide potential of agroecological mixtures in the control of Ascia monuste orseis. The experiment was carried out in the laboratory, in a completely randomized experimental design, with five treatments  and ten repetitions, where each repetition consisted of five caterpillars. The cabbage leaves collected in the agroecological property were sectioned in oval shape and immersed for a time of 2 minutes in the respective syrups. Subsequently, five fifth-instar caterpillars were transferred to each plate containing the leaves treated with the syrups. The evaluated parameters were the mortality of the caterpillars 24 and 72 h after the application of the agroecological mixtures. For the caterpillars that survived after this period of exposure to the syrups, the pupa stage and adult emergence were evaluated. Data were submitted to the Kruskal-Wallis non-parametric test at a significance level of 5%. If there were significant differences between treatments, the medians were compared by Dunn's test at 5% probability of error. The tobacco and neem syrups had a significant effect on the mortality of curuquerê caterpillars. Regarding the duration of the pupal phase, the tobacco, garlic + pepper and sage mixtures showed a significant difference when compared to the control. When the emergence was evaluated, it was verified that all the mixtures tested presented a reduction in the emergence of the adults and differed significantly from the control. The results of this work demonstrate the efficiency, mainly for tobacco syrup, as a potential insecticide for the control of caterpillars of Ascia monuste orseis.